STUDY OF STRESS-STRAIN RELATIONSHIP OF CONCRETE WITH SILICA FUME ADDED AS PARTIAL REPLACEMENT FOR CEMENT - Luthfiana, Haya; Wibowo, Wibowo; Safitri, Endah (Jurnal Teknik Sipil, 2024)
This study investigates the stress-strain relationship of concrete with silica fume used as a partial replacement for cement, aiming to enhance concrete quality and durability. Silica fume, acting as a cement substitute, fills voids between cement particles, reducing pore size and enhancing concrete properties. Concrete specimens were prepared with varying silica fume content (0% to 20%) and subjected to rigorous testing using Compression Testing Machines (CTM). Results indicate a significant 55.91% increase in compressive strength with 10% silica fume, compared to conventional concrete. Beyond this optimal point, compressive strength diminishes due to reduced pore volume. Moreover, silica fume influences stress and strain characteristics, with higher maximum stress and strain observed in silica fume concrete. The research employs polynomial equations to model the stress-strain relationship post-peak stress, revealing valuable insights for concrete design and performance prediction. This study underscores the importance of silica fume as a beneficial additive, contributing to concrete strength and durability. Further investigation is needed to fully understand the mechanical properties and optimize the use of silica fume in concrete construction, ensuring improved performance and longevity of concrete structures.